PENGARUH HARGA DAN KERAGAMAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN DI WARUNG KELONTONG KENNAN, DESA KEDUNGSARI, KECAMATAN PENGASIH, KABUPATEN KULON PROGO, DAERAH ISTIMEWA YOGYAKARTA - Setiawan, Edi; Puspitaningrum, Sindi (PRIMA EKONOMIKA, 2026)
The aim of this research is to determine the partial or simultaneous influence of Price and Product Diversity on Purchasing Decisions at Kennan Grocery Stall, Kedungsari Village, Pengasih District, Kulon Progo Regency, Special Region of Yogyakarta. The type of research used in this research is quantitative research which aims to confirm the data obtained. The sampling technique used was accidental sampling with a total of 100 respondents. This research was conducted at Warung Kelontong Kennan, Kedungsari Village, Pengasih District, Kulon Progo Regency, Special Region of Yogyakarta. The data collection technique used was using a questionnaire technique. The data obtained was then processed using SPSS version 25. This analysis included instrument tests, classical assumption tests, multiple linear regression tests, hypothesis tests and F tests, as well as coefficient of determination tests (Adjusted R Square). Based on the t test data analysis carried out in this research, it can be seen that the price variable has a sig value of 0,000 < 0,05 so that H1 is accepted, which means that the price variable influences purchasing decisions at the Kennan Grocery Shop. Product Diversity has a sig value of 0,000 < 0,05 so that H2 is accepted, which means that the Product Diversity variable influences purchasing decisions at the Kennan Grocery Shop. Based on the results of the F test, the price variable and product diversity variable have a significance of 0,000 < 0,05, so H3 is accepted, which means that price and product diversity have a strong influence on purchasing decisions. The results of the determination test show that the Adjusted R Square value is 37,9%, meaning that the purchasing decision variable (Y) is 37,9% determined by price, product diversity, and 62,1% is determined by other variables not included in this research. Keywords: Purchase Decision, Price, Product Diversity.